Peran Model Pembelajaran Kontekstual Dalam Mendukung Pengelolaan Pembelajaran Aktif, Bermakna, dan Berpusat pada Siswa - Ronald Evandi Aden; Cindi Anisa Bahar; Melli Sandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the role of the contextual teaching and learning (CTL) model in supporting teachers to create active and meaningful learning experiences. The research highlights the importance of linking instructional content with students’ real-life contexts to strengthen conceptual understanding and improve problem-solving abilities. Through descriptive analysis, this paper outlines the main components of CTL, including constructivism, inquiry, questioning, learning communities, modeling, reflection, and authentic assessment. The findings show that the CTL model enables students to construct knowledge independently, apply concepts to practical situations, and develop critical thinking skills. Furthermore, this study describes challenges faced by teachers across educational levels—such as limited time, students’ low independence, and variations in academic abilities—and proposes practical solutions to address them. The implications of this study emphasize the need for teachers to design engaging learning activities, build supportive classroom environments, and integrate authentic assessment to measure students’ holistic progress. Overall, CTL serves as an effective model for enhancing learning relevance, increasing student participation, and preparing learners to face real-world challenges.